Sintesis BaM/PAni Doping Cu Optimasi Sifat Radar Absorbing Material Pada Aplikasi Pelapisan Alpalhankam - Aritonang, Sovian; Xaviera, Allodya Nadra; Devina, Ardelia; Br Panjaitan, Thesalonika; Nareswari, Vania Agatha (Rekayasa Material, Manufaktur dan Energi, 2024)
Defense technology known as stealth technology aims to reduce the response of electromagnetic waves emitted by radar so that the position or location of an object is not detected. Barium Hexaferite has properties as a Radar Absorbing Material (RAM). Research on radar absorbing matrial from barium hexaferite already exists, but those using cu doping do not yet exist. In order to increase the effectiveness of its absorption, Barium Hexaferite is doped with Cu metal synthesized by coprecipitation method. Aniline polymerization was carried out with BaM to form BaM/PAni composite. Characterization of composite synthesis samples and coating results were carried out by SEM, FTIR, LCR-meter, and VNA to identify chemical bonds, electrical conductivity properties, microstructure, and reflection loss properties of RAM composite samples. Based on the results of previous research, the optimal absorption of multilayer coatings on steel with a reflection loss of -49.028 dB was obtained with an absorption frequency of 8.2 GHz. The addition of Cu doping is expected to improve the material's ability to absorb radar waves and reduce object reflections.